Kinematic hydrology and modelling - Stephenson, David, 1943- (Developments in water science, 1986)
Requiring little mathematical background, the book provides tools for hydraulic engineers and hydrologists concerned with estimating catchment runoff and floods. It condenses widely spread research literature on the subject of kinematic hydrology and emphasizes basic principles so it should be of value to students and teachers in these areas. The book is comprehensive and yet written in a basic way enabling practitioners to pick out relevant sections and apply them to real problems. It also contains a valuable collection of charts and equations as well as simple computer programs for modelling catchment runoff and stream flow using the kinematic equations. A wide spectrum of hydrological processes can be analyzed using the kinematic equations. Overland flow, stream flow and even groundwater flow can be studied. A review of the assumptions behind the theory indicates where alternative equations are more accurate. The book thus provides tools for hydrological simulation, stormwater system design and catchment management. It will be particularly useful for professors and students in postgraduate and senior years in hydrology, and practicing engineers and hydrologists in stormwater, flood and water resources fields.